1991
DOI: 10.1073/pnas.88.14.6259
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a ouabain-like compound from human plasma.

Abstract: The plasma membrane sodium-potassium pumps that regulate intracellular sodium in most animal cells have specific, high-afimity receptors for the digitalis glycosides and their aglycones. This has fostered speculation that there is an endogenous ligand. We have purified and structurally identified by mass spectroscopy an endogenous substance from human plasma that binds with high affinity to this receptor and that is indistinguishable from the cardenolide ouabain. This human ouabain-like compound (OLC) displace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
467
2
11

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 705 publications
(496 citation statements)
references
References 29 publications
(29 reference statements)
6
467
2
11
Order By: Relevance
“…Because there is sufficient evidence that ouabain and marinobufagenin are likely the endogenous cardiotonic steroids, our findings brings about an interesting question as to whether this mode of regulation is relevant to in vivo physiology. To this end, several laboratories have reported that endogenous ouabain and marinobufagenin are circulated at sub-nM to nM concentrations in normal individuals and that volume expansion can significantly increase their concentrations (Hamlyn et al, 1991;Fedorova et al, 2002;Bauer et al, 2005). Thus, it is conceivable that the described regulation may be relevant to in vivo physiopathology if future in vivo studies confirm our in vitro experiments.…”
Section: Regulation Of Plc-␥1 and Ip3r2 By The Activated Na/katpase Ssupporting
confidence: 58%
“…Because there is sufficient evidence that ouabain and marinobufagenin are likely the endogenous cardiotonic steroids, our findings brings about an interesting question as to whether this mode of regulation is relevant to in vivo physiology. To this end, several laboratories have reported that endogenous ouabain and marinobufagenin are circulated at sub-nM to nM concentrations in normal individuals and that volume expansion can significantly increase their concentrations (Hamlyn et al, 1991;Fedorova et al, 2002;Bauer et al, 2005). Thus, it is conceivable that the described regulation may be relevant to in vivo physiopathology if future in vivo studies confirm our in vitro experiments.…”
Section: Regulation Of Plc-␥1 and Ip3r2 By The Activated Na/katpase Ssupporting
confidence: 58%
“…This could be the rationale for colocalization of high ouabain affinity Na ϩ pumps and Na ϩ ͞Ca 2ϩ exchangers in these PM areas. This might reveal how an endogenous ouabain isomer (12,(37)(38)(39), which circulates at nanomolar concentrations (40) and is present in the brain (38,39), could, by modulating the activity of these high ouabain affinity Na ϩ pumps (28,37), play a role in many physiological, and even pathophysiological, processes (12). Finally, this may also explain why the isoformspecific features of the ouabain binding regions of ␣2 and ␣3 have been so well conserved during the evolution of higher animals (4,10).…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] Previous studies have shown that EO is mostly produced in the adrenal cortex and circulating EO activate the sympathetic nervous system. 3,4 Their results suggested that these activations can be inhibited with b-blocker, angiotensin converting enzyme inhibitor and digoxin immune fab (antigen-binding fragments), Digi-Bind.…”
Section: Introductionmentioning
confidence: 99%